An Unusual Case of Abdominal Pain in the Postpartum Period: A Case Report of Vernix Caseosa Peritonitis - Rawa Amin; Justin Cruz; Jin Lee (Annals of Internal Medicine: Clinical Cases)
Vernix caseosa peritonitis is a rare cause of peritonitis that can occur in the postpartum period. We present a case of diffuse abdominal pain 5-week postpartum that was unrelieved with antibiotics. Computed tomography of the abdomen showed phlegmonous peritonitis with nodularities. Omental node biopsy revealed necroinflammatory debris and multinucleate giant cells suggesting a noninfectious granulomatous process. Treatment with steroids resulted in significant improvement and decreased nodularity. Vernix caseosa peritonitis is caused by an inflammatory response attributable to maternal amniotic fluid spilling into the peritoneal cavity. It should be considered in the differential diagnosis of postcesarean acute abdomen thereby avoiding laparotomy and the unnecessary work-up and treatment.